Mapping Intersects of Power and Reciprocity in Adult EducationDeliberative Civic Engagement and Leadership Development in Community-Engaged Scholarship - Katherine L. Davis; Brandon W. Kliewer; Aliki Nicolaides (Adult Education Research Conference, 2015)
The purpose of this work is to assist in identifying and naming dynamic relational forces that shape the effectiveness of community engagement. Understanding power from the perspective of reciprocity supports adaptive and transformational learning necessary to increase the effectiveness of community-engaged partnerships and scholarship.
Keywords: engaged scholarship; deliberative civic engagement; reciprocity; power